The Nature of Knowledge in the Context of Islamic Educational Philosophy - Ahmad Fauzan; Maspuroh; Fahir Ali; Tia Esapitri; Yopa Nurlaela (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2025)
This article discusses the nature of science in the context of Islamic educational philosophy using the literature method. Science is not only understood as a collection of facts, but as a process that involves the mind, heart and senses. Through a critical approach, this research identifies sources of knowledge which include insaniyah, qauliyah, and kauniyah verses in achieving the ultimate goal of the search for marifatullah knowledge or knowledge about Allah.